Health-related quality of life in patients with Primary Sjögren's Syndrome and Xerostomia: a comparative study - Rostron, Jocelyne; Rogers, Simon; Longman, Lesley; Kancy, Sue; Field, E Anne (Gerodontology, 2002)
Objective: To compare the health status of groups of Primary Sjögren's and Xerostomia patients, using the Medical Outcomes Short Form 36 (SF‐36). The SF‐36 is a generic measure, divided into eight domains, used in the assessment of health‐related quality of life. Patients and methods: The SF‐36 was given to 2 groups: Group 1 comprised 43 patients diagnosed with Primary Sjögren's Syndrome (1SS) and an unstimulated whole salivary flow rate (UFR) of <0.1 ml/min). Group 2 (n = 40) reported Xerosiomia but had an UFR >0.2 ml/min. Sub groups of patients in Groups 1 and 2 were compared with community normative data, for the SF‐36 Results: There were trends to suggest lower SF36 scores for 1SS patients but there were no significant differences between the mean domain scores of Groups 1 and 2. 1SS and Xerostomia patients registered lower mean scores across all 8 domains, compared with normative community data. Conclusion: The SF‐36 was unable to detect significant differences between subjects with 1SS and Xerostomia but a larger sample size is required to confirm these findings. The results of this limited study suggest that a disease‐specific measure is required to assess the impact 1SS on health‐related Quality of life (QOL).